A comparison of alternative measures of organizational aspirations - Bromiley, Philip; Harris, Jared D. (Strategic Management Journal, 2014)
Research on organizational aspirations has used various representations of firm‐level aspirations and based those representations on various performance measures. To advance our understanding of the measurement of aspirations, we empirically compare three different aspiration models defined using six different performance measures to explain three different firm outcomes (financial misrepresentation, R&D spending, and income‐stream uncertainty). The results moderately support a model with separate historical and social aspirations over a model of aspirations that systematically switches between the two. The results strongly support both the separate and switching models over a model where aspirations constitute a weighted average of historical and social comparisons, the model associated most directly with C yert and M arch's original specification. We discuss the implications of these results and highlight directions for future research . Copyright © 2013 John Wiley & Sons, Ltd.